DEVELOPMENT OF HEALTH LITERACY PROMOTING PROGRAM ABOUT PARTICULATE MATTERS FOR SECONDARY SCHOOL STUDENTS - Phungkat, Yanisa; Sarayuthpitak , Jintana; tingsabhat, Suthana; Rodpipat, Sarinya (Academic Journal of Thailand National Sports University, 2022)
The purpose of this research was to develop a health literacy promotion program about particulate matters for secondary school students. The research methodology was divided into 4 phases; phase 1, reviewing of the research literature on concept of particulate matters the health literacy promotion and health literacy assessment, phase 2, analyzing concept of Phenomenon Based Learning and Blended Learning. A health literacy promotion program about particulate matters, phase 3, an expert analysis of the quality of the program by five experts included 1) assessment form for content validity, activity components 2) content validity evaluation of 8 activities and 3) an evaluation form for content validity of the developed program. The results showed that index of congruence of the program consisted of the activity title, purpose, conceptual framework, and the steps in each activity were 0.82. This program had 8 activities i.e., 1) enhance knowledge 2) reliable channel 3) dust communication 4) my ability 5) fake or not 6) my decision 7) mind game and 8) สearn creatively. The average mean of index of congruence was 1.00. The program was set for 8 weeks, 2 days per week, and 1 hour per day. The index of congruencies of the overall program was 1.00. This program was determined to promote secondary school health literacy about particulate matters.